2020
DOI: 10.1161/strokeaha.120.029996
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Abnormalities in Spontaneous Subarachnoid Hemorrhage

Abstract: Background and Purpose: We investigated white matter abnormalities in patients with spontaneous subarachnoid hemorrhage following aneurysmal rupture, by using tract-based spatial statistics. Methods: Sixteen patients with spontaneous subarachnoid hemorrhage due to aneurysmal rupture and 18 age- and sex-matched healthy control subjects were recruited. Voxel-wise statistical analysis of fractional anisotropy data was performed by using tract-based spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…By using DTI, many studies have reported SAH-related neural tract injuries [ 36 , 43 55 ]. However, few studies have assessed the influence of SAH on the entire brain white matter, and recently, Jang et al (2020), by applying TBSS, demonstrated that spontaneous SAH following aneurysmal rupture can induce abnormalities in extensive areas of the subcortical white matter [ 36 ]. However, the majority of these previous studies are related to spontaneous aneurysmal SAH, and little has been reported on the neural injuries associated with traumatic SAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using DTI, many studies have reported SAH-related neural tract injuries [ 36 , 43 55 ]. However, few studies have assessed the influence of SAH on the entire brain white matter, and recently, Jang et al (2020), by applying TBSS, demonstrated that spontaneous SAH following aneurysmal rupture can induce abnormalities in extensive areas of the subcortical white matter [ 36 ]. However, the majority of these previous studies are related to spontaneous aneurysmal SAH, and little has been reported on the neural injuries associated with traumatic SAH.…”
Section: Discussionmentioning
confidence: 99%
“…DTI data were obtained at an average of 12.43±12.36 months after SAH onset by using a 1.5 T Philips Gyroscan Intera device (Hoffman-LaRoche, Best, Netherlands) with 32 non-collinear diffusion-sensitizing gradients by performing single-shot echo-planar imaging. For the 32 non-collinear diffusion-sensitizing gradients, 65 consecutive slices were obtained parallel to the anterior commissure – posterior commissure line [ 36 ]. Imaging parameters were as follows: acquisition matrix=96×96, reconstructed to matrix=192×192 matrix, field of view=240×240 mm, repetition time=10,398 ms, echo time=72 ms, echo-planning imaging factor=59 and b =1000 s/mm 2 , slice gap=0, and slice thickness=2.5 mm [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each of the 32 non-collinear diffusion-sensitizing gradients, 65 contiguous slices were acquired parallel to the anterior or posterior commissure line. 27 The imaging parameters were as The Oxford Centre for Functional Magnetic Resonance Imaging of the Brain Software Library (FSL; www.fmrib.ox.ac.uk/fsl) (FSL version 5.0, FMRIB, Oxford, UK) was used to analyze the diffusion-weighted imaging data. Affine multiscale two-dimensional registration was applied to correct the head motion effect and image distortion due to eddy currents.…”
Section: Diffusion Tensor Imaging and Tractographymentioning
confidence: 99%
“…Therefore, the study of white matter injury after SAH may be of more importance than we currently know. Lee et al found extensive white matter abnormalities in SAH patients through tract-based spatial statistical analysis, but not in retrolenticular parts of the internal capsule, right superior longitudinal fasciculus, or right superior corona radiata (10), providing important data support for the accurate diagnosis of the presence and severity of nerve injury in patients with subarachnoid hemorrhage. Clinical studies did find different types of white matter lesions in SAH patients.…”
Section: White Matter Injury After Sahmentioning
confidence: 99%